Aivilik Inuit woman with Tununermiut tattoos, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1904)
A young Inuit woman identified as a member of the Aivilik group, poses in traditional dress in front of a white back-cloth at Cape Fullerton, Hudson Bay, February 18, 1904. What appear to be tattoos are visible on her face. The image is identified as: ".showing the tattooing of the Tunuma [Tununermiut] tribe (Ponds Bay)." Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo 116. The number 40 is etched into lower right of emulsion on plate. The Aivilik, or Aivillingmiut, are a group of Iglulik Inuit. These Inuit of the west coast region of Hudson Bay were closely associated with Captain George Comer and the American whalers for many years. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. This is one of a group of photos taken by Comer to record facial tattooing of various Inuit groups of Hudson Bay. He had Aivilik women paint their faces to simulate the tattooing styles of various other groups, in this case, the Tununermiut.